Implementation Of Heavy Equipment Rental Agreements Between The Renter And CV. Yoga Rental In Bengkulu City - Yoga Faruncha; Uswatun Hasanah; Sherly Nelsa Fitri; Desy Maryani (JURNAL HUKUM SEHASEN, 2023)
CV. Yoga Rental in Bengkulu City is one of the CVs engaged in heavy equipment rental. Often there are problems in the lease agreement between tenants and CV. Yoga Rental In Bengkulu City. One of them is the late payment by the lessee. The problem to be discussed in this study is whether the implementation of the heavy equipment rental agreement between the lessee and CV. Yoga Rental in Bengkulu City is in accordance with the Civil Code and is the settlement of default on the heavy equipment rental agreement between the tenant and CV. Yoga Rental in Bengkulu City is in accordance with the Civil Code. In this study the authors use the type of empirical legal research. The sample in this research is 1 (one) owner of CV. Yoga Rental In Bengkulu City, 3 (three) employees of CV. Yoga Rental in Bengkulu City and 3 (three) heavy equipment renters at CV. Yoga Rental In Bengkulu City. To answer the formulation of the problem, it can be concluded that: 1. That the implementation of the heavy equipment rental agreement between the tenant and CV. Yoga Rental in Bengkulu City has been carried out in accordance with the applicable provisions where the agreement uses a written rental agreement because it provides certainty about the rights and obligations of the parties who make it. Settlement of the occurrence of Default in the implementation of the heavy equipment rental agreement at CV. Yoga Rental is based on what was conveyed by the owner of CV. Yoga Rental, namely tenants who delay paying rent will result in the withdrawal of heavy equipment, but all problems will still be discussed in deliberation to get the best solution